Reconstruction of Pre-Trial Procedure Law Regulation Based on Justice Values - Sari, Pebrina Permata; Wahyuningsih, Sri Endah; Bawono, Bambang Tri; Mashdurohatun, Anis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
The purpose of this study is to analyze and find related to pre-trial procedural law regulations that are not yet based on justice values, to analyze and find weaknesses in current pre-trial procedural law regulations, and to find a reconstruction of pre-trial procedural law regulations based on Justice Values. There are 3 (three) theories used, namely the Pancasila justice theory as a grand theory, the legal system theory as a middle theory, and the progressive legal theory as an applied theory. This research method uses a socio-legal approach method that law is both a norm and a behavior that examines social phenomena. The analysis of research data is descriptive qualitative. The location of the research was conducted at the Kuala Kapuas District Court. The data source is from the Judge at the Kuala Kapuas District Court. "Mistakes that are made repeatedly over a long period of time will turn into truth." This expression is appropriate in the practice of handling pre-trial cases. Since the birth of the pre-trial institution in Law No. 8 of 1981 concerning Criminal Procedure Law (KUHAP) 38 years ago, the practice of pre-trial seems to use civil procedural law. Such as summons and notifications are carried out by bailiffs. The stages of the process are similar to civil trial trials. Normatively, the Criminal Procedure Code does not strictly regulate pre-trial procedural law. In the Criminal Procedure Code, there is also no article that mentions pre-trial cases with civil case mechanisms. In addition, from the registration and use of case codes in the Court alone, it is clear that pre-trial is a criminal case. It is reasonable that until now the pre-trial examination mechanism only refers to the customs applied in court practice, because since the Criminal Procedure Code was formed it has been handed over to the regulatory mechanism based on court policy. Judges may not reject cases on the basis that there is no procedural law. With the assumption and approach that pre-trial cases have the same nature and characteristics as civil cases, the Judge uses examination procedures as in civil cases even though pre-trial cases are actually criminal cases as seen from the use of the register and code listed in the case number.